The Identification of On Job Training (OJT) Problems among Malaysian Vocational College Construction Technology Students - Abdul Musid, Nurhafizah; Mohd Affandi, Haryanti; Firdaus Mustaffa Kamal, Mohd; Amin Nur Yunus, Faizal (International Journal of Engineering and Technology, 2018)
On Job Training (OJT) is one of the requirements to acquire Diploma Vokasional Malaysia for Vocational College (VC) students.  However, there are a few problems among students during their OJT such as lack of leadership and technical skills. This paper examines problems among the Vocational College Construction Technology students’ during their OJT. The research design for this study is a case study that is analyzed through qualitative method.  The instrument used in this preliminary research is a semi-structured interview that involved Construction Technology lectures, students, and the construction practitioners. From the data analysis, four major problems have been identified which are the assessment in OJT, duration of OJT, OJT placement and job scope at the workplace, syllabus, and type of technologies used in VC.  This study shows lacking in the execution of OJT for Diploma in Construction Technology and need to be improved.  Therefore, further research is suggested to be conducted in studying the competency level of Malaysian Vocational College Construction Technology students after they undergo OJT.